Interface Strength of Piles Embedded in Frozen Soils - Zuhao, Jin (Université d'Ottawa / University of Ottawa, 2018)
In this study, the effect of normal stress acting on a model scale pile is determined experimentally. The minimum soil temperature was -5 degrees Celcius. Additional experiments were conducted to determine the adfreeze bond strength of an interface between the Cornwall sand and a galvanized steel plate. These tests were done using a conventional direct shear apparatus. In order to conduct interface tests under freezing temperatures, some modifications were made on the direct shear apparatus. In these experiments, three different normal stresses and three different water contents were used. The present study was extended to investigate whether there was any agreement between the adfreeze strength measured in the present study and the adfreeze strength calculated from the pull-out tests by Villeneuve (2017).
Keywords: interface; Strength; Frozen; Soils; Piles